Contributions of a minerals industry cluster to sustainable development: A case study on human and social capital in Richards Bay, South Africa - Kato, Shuhei (Department of Chemical Engineering, 2017)
The South African economy has developed with its strong connection to the minerals extraction and processing industries. Rich endowments of coal and a well-established mining sector in the country enabled the generation and supply of competitively priced electricity to energy and capital intensive processing and chemical industries. Although the minerals industry cluster remains globally competitive at the present time, whether it can be a catalyst for sustainable development, economically, socially and environmentally is in question. Field work was carried out in Richards Bay to analyse the development contributions of the local aluminium industry cluster in terms of two of the five capitals essential for sustainable development, viz. human and social capital. This town is the host of world class aluminium smelters as well as mineral sands mining and smelting, amongst other energy intensive industries such as paper pulp and phosphate production. The analysis interrogates the importance of skills development and of collective action between various stakeholders centred on the Hillside smelter of South 32, and including interviews with representatives of ten further stakeholders. Evidence found shows that the minerals industry cluster has contributed to human capital development, and continues to do so, through well-established in-house training and mentorship programmes as well as their corporate social investment into enterprise and supplier development, education and primary health care. However, a more competitive and environmentally responsible industrial cluster would require continuous improvement through institutional and individual capabilities. Research and training institutions and government intervention have important roles to play in this regard. One of the major challenges is rooted in the lack of social capital development in the past. Although no single accepted definition nor standard for measuring exists, social capital can be defined as the norms and networks that enable people to act collectively. The racially segregated development pattern in the region had left residents with huge disparities and a trust deficit. This mitigated against collective actions within the community except in the few cases of natural disaster responses and crime prevention. This is evidenced in the free-riding of skilled labourers by some companies in the region and the failure of socio-economic development programmes in the past due to the low level of community buy-in. The research highlights that the significance of the local minerals industry cluster remains undoubtedly high; however, a facilitative process of social capital development is necessary to promote collective actions. The process requires accountable formal institutions who can mitigate social distrust, create dialogue and a cooperative environment between different interest groups. This is particularly important as the government resource-based industrialisation policy is centralised in developing linkages from extractive sector (downstream, upstream, and side-stream) but little attention has been paid to the aspect of social capital development. It is expected that the study itself contributes to social capital development and works as a communication platform to further promote studies in applying multidisciplinary learning-by-doing process across academia, policymakers, and practitioners.